The Integration of Wallachia and Moldavia into the Ottoman Danube Flotilla: Material, Labour, and Fiscal Obligations - Yıldırım, Filiz (Yücel ÖZTÜRK, 2025)
From its early period, the Ottoman state structured its political and military expansion primarily towards the Balkans and Central Europe. One of the most sensitive components of this strategy was the objective of establishing control over the Danube River, which functioned as the principal corridor of transportation and supply for the region. Taking into account both the opportunities and constraints of the Danube, the state developed a naval formation adapted to riverine conditions and, in doing so, constructed a distinct military-logistical capacity that shaped its influence in both the Balkans and Central Europe. Ottoman dominion over the Danube gradually acquired an institutional framework through the incorporation of Wallachia, Moldavia, and to some extent Transylvania, located north of the river, into the Ottoman political order. These tributary principalities were obligated not only to pay annual tribute but also to supply, in kind, the materials and labour required by the Ottoman centre. A significant portion of the construction and equipment needs of the Danube Flotilla—including timber, masts and spars, beams, nails, pitch, tar, resin, wild vine rods, charcoal, tallow, moss, oars, hemp rope, cordage, and beeswax—was supplied from Wallachia and Moldavia. In certain periods, the direct construction and delivery of ready-to-use vessels also formed part of these obligations. These contributions were not limited to material supply alone. Skilled craftsmen such as carpenters (neccar), joiners (dülger), caulkers, blacksmiths (haddâd), sawyers, bridge-builders, and millers, as well as labour groups engaged in physically demanding tasks—namely cerahors, rençbers, and prostoykas—were systematically mobilised as part of this structure. Consequently, Wallachia and Moldavia came to function not merely as auxiliary supply zones, but as logistical and labour nodes directly integrated into the production, maintenance, and operational processes of the Danube naval system. Drawing primarily on archival documents as well as contemporary sources and modern scholarship, this study examines the institutional roles undertaken by Wallachia and Moldavia in relation to the Ottoman Danube Flotilla and analyses the multilayered structure reflected in the circulation of materials, labour, and financial resources. In so doing, it demonstrates that these principalities, far from being peripheral or passive tributary territories, constituted integral and constitutive components of the river-based military and logistical architecture of the Ottoman state.

Osmanlı Devleti siyasî ve askerî yayılmasını erken dönemden itibaren Balkanlar ve Orta Avrupa istikametinde kurgulamış; bu stratejinin en hassas unsurlarından birini, bölgenin ana ulaştırma ve ikmal hattı konumundaki Tuna Nehri üzerinde hâkimiyet tesis etme hedefi oluşturmuştur. Devlet, Tuna’nın imkân ve sınırlılıklarını gözeterek nehir şartlarına uygun bir donanma teşkil etmiş ve böylece Balkanlar ile Orta Avrupa’da etkisini hissettiren özgün bir askerî-lojistik kapasite inşa etmiştir. Tuna üzerindeki bu hâkimiyet, nehrin kuzeyindeki Eflak, Boğdan ve kısmen Erdel bölgelerinin Osmanlı siyasal alanına dâhil edilmesiyle kurumsal bir çerçeve kazanmıştır. Haraçgüzar statüdeki bu prenslikler, yıllık vergi yükümlülüklerinin yanı sıra merkezin ihtiyaç duyduğu malzemeleri ve iş gücünü aynî biçimde teminle mükellef kılınmıştır. Tuna İnce Donanması’nın inşa, bakım ve donanım süreçlerinde kullanılan kereste, sütun/direk, seren, çivi, zift, katran, reçine, yaban asma çubukları, kömür, don yağı, yosun gibi yapı malzemeleri ile kürek, kınnab, halat ve balmumu gibi donanım unsurlarının önemli bir kısmı Eflak ve Boğdan’dan sağlanmış; bazı dönemlerde doğrudan gemi inşası ve hazır gemi teslimi de bu yükümlülüklerin parçası haline gelmiştir. Bu katkı yalnızca malzeme tedarikiyle sınırlı kalmamış; neccar, dülger, kalafatçı, haddâd, bıçkıcı, köprücü ve değirmenci gibi nitelikli ustaların yanı sıra cerahor, rençber ve prostoyka gibi yoğun emek gerektiren işlerde istihdam edilen grupların seferber edilmesiyle emek boyutunda da kurumsallaşmıştır. Böylece Eflak ve Boğdan, Tuna üzerindeki tersaneler, köprü sistemleri ve sefer dönemlerindeki zahire-mühimmat nakliyatı açısından, donanma düzeninin yalnızca yardımcı bir arka alanı değil, doğrudan üretim ve işletme süreçlerine eklemlenen birer lojistik ve emek düğümü haline gelmiştir. Bu çalışma, arşiv vesikaları başta olmak üzere çağdaş kaynaklar ve araştırma eserlerinden hareketle, Eflak ve Boğdan’ın Tuna İnce Donanması için üstlendiği kurumsal rolleri; bu rollerin malzeme, iş gücü ve mali kaynak akışına yansıyan çok katmanlı yapısını incelemektedir. Böylece söz konusu prensliklerin Osmanlı Tuna donanma sisteminde, klasik haraçgüzar-taşra tasnifinin ötesine geçerek, nehir temelli askerî ve lojistik mimarinin kurucu bileşenleri arasında yer aldığı ortaya konulmaktadır.
Eflak ve Boğdan’ın Tuna Nehri Donanması’na Entegrasyonu: Malzeme, Emek ve Mali Yükümlülükler
Keywords: Early Modern Balkan History; Yeniçağ Balkan Tarihi